Modified grape composition under climate change conditions requires adaptations in the vineyard - Van Leeuwen, Cornelis; Destrac-Irvine, Agnès (OENO one, 2017)
Aim: Major effects of climate change are an increase in temperature, a modification in rainfall patterns and an increase in incoming radiations, in particular UV-Bs. Grapevines are highly sensitive to climatic conditions. Hence, plant development, grape ripening and grape composition at ripeness are modified by climate change. Some of these changes are already visible and will be amplified over the coming decades; other effects, although not yet measurable, can be predicted by modeling. The objective of this paper is to assess which modifications in wine quality and typicity can be expected and what levers growers can implement to adapt to this changing situation. Methods and results: This paper focusses on the effect of temperature, vine water status and UV-B radiation in viticulture. Vine phenology is driven by temperacture. A significant advance in phenology (i.e. budburst, flowering and veraison dates) has been observed since the early 1980’s in most winegrowing regions. The combined effect of advanced phenology and increased temperatures results in warmer conditions during grape ripening. In these conditions, grapes contain more sugar and less organic acids. Composition in secondary metabolites, and in particular aromas and aroma precursors, is dramatically changed. Increased drought, because of lower summer rain and/or because of higher reference evapotranspiration (ET0), induces earlier shoot growth cessation, reduced berry size, increased content in skin phenolic compounds, lower malic acid concentrations and modified aroma and aroma precursor profiles. Increased UV-B radiation enhances the accumulation of skin phenolics and modifies aroma and aroma precursor profiles. Over the next decades, an amplification of these trends is highly likely. Major adaptations can be reached though modifications in plant material (grapevine varieties, clones and root stocks), vineyard management techniques (grapevine architecture, canopy management, harvest dates, vineyard floor management, timing of harvest, irrigation) or site selection (altitude, aspect, soil water holding capacity). Conclusion: Climate change will induce changes in grape composition which will modify wine quality and typicity. However, these modifications can be limited through adaptations in the vineyard. Significance and impact of the study:  This study assesses the impact of major climatic parameters (temperature, water and radiation) on vine physiology and grape ripening. It addresses the issue of how the expected changes under climate change will impact viticulture. It is shown that appropriate levers do exist to allow growers to adapt to this new situation. Among these, modifications in plant material and viticultural techniques are the most promising tools.